Quality of Service and Segmentation in the MICE Industry: An Approximation based on Fuzzy Logic. - Gonzaga Vallejo, L. (2016)
This article aims to address a multi-dimensional problem in the service industry: the quality assessment experienced at academic conferences held at the Universidad Técnica Particular de Loja (UTPL) Ecuador, in the year 2013. Our approach is based on fuzzy logic and calculates a global customer satisfaction index for specific market segments: gender, nationality and age. The problem of linguistic ambiguity is addressed by applying Fuzzy Triangular Numbers (FTN). The quality indicator is also based on the concept of close resemblance to an ideal solution. The questionnaire, which contained 32 different dimensions, has been used to evaluate the level of satisfaction that the delegates experienced. The results show that the analyzed segments produce varying levels of satisfaction. In addition, we analyzed the most influential factors that affected the service quality evaluation. Current literature indicates that there have been limited studies done about the quality of service that is provided in conference tourism. Our results can be applied regardless of the organizers and the key authorities of the university, or the planners and administrators of the city. In this way, we can improve the competitiveness of Loja and that of UTPL thus making it an attractive destination for academic conferences and meetings.